Music Memory Following Short-term Practice and Its Relationship with the Sight-reading Abilities of Professional Pianists - Aiba, Eriko; Matsui, Toshie (Frontiers in Psychology, 2016)
This study investigated the relationship between the ability to sight-read and the ability to memorize a score using a behavioural experiment. By measuring the amount of memorization following short-term practice, we examined whether better sight-readers not only estimate forthcoming notes but also memorize musical structures and phrases with more practice. Eleven pianists performed the music first by sight-reading. After a 20-minute practice, the participants were asked to perform from memory without any advance notice. The number of mistakes was used as an index of performance. There were no correlations in the numbers of mistakes between sight-reading and memory trial performance. Some pianists memorized almost the entire score, while others hardly remembered it despite demonstrating almost completely accurate performance just before memory trial performance. However, judging from the participants’ responses to a questionnaire regarding their practice strategies, we found auditory memory was helpful for memorizing music following short-term practice.